Interconnected Clinical and Social Risk Factors in Breast Cancer and Heart Failure - Sinha, Arjun; Bavishi, Avni; Hibler, Elizabeth A.; Yang, Eric H.; Parashar, Susmita; Okwuosa, Tochukwu; DeCara, Jeanne M.; Brown, Sherry-Ann; Guha, Avirup; Sadler, Diego; Khan, Sadiya S.; Shah, Sanjiv J.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Breast cancer and heart failure share several known clinical cardiovascular risk factors, including age, obesity, glucose dysregulation, cholesterol dysregulation, hypertension, atrial fibrillation and inflammation. However, to fully comprehend the complex interplay between risk of breast cancer and heart failure, factors attributed to both biological and social determinants of health must be explored in risk-assessment. There are several social factors that impede implementation of prevention strategies and treatment for breast cancer and heart failure prevention, including socioeconomic status, neighborhood disadvantage, food insecurity, access to healthcare, and social isolation. A comprehensive approach to prevention of both breast cancer and heart failure must include assessment for both traditional clinical risk factors and social determinants of health in patients to address root causes of lifestyle and modifiable risk factors. In this review, we examine clinical and social determinants of health in breast cancer and heart failure that are necessary to consider in the design and implementation of effective prevention strategies that altogether reduce the risk of both chronic diseases